2012
DOI: 10.1002/aur.1224
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual and Neural Response to Affective Tactile Texture Stimulation in Adults with Autism Spectrum Disorders

Abstract: Autism spectrum disorders (ASD) are associated with differences in sensory sensitivity and affective response to sensory stimuli, the neural basis of which is still largely unknown. We used psychophysics and functional magnetic resonance imaging (fMRI) to investigate responses to somatosensory stimulation with three textured surfaces that spanned a range of roughness and pleasantness in a sample of adults with ASD and a control group. While psychophysical ratings of roughness and pleasantness were largely simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
95
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(111 citation statements)
references
References 76 publications
12
95
2
Order By: Relevance
“…Thus, the OXTmediated increase in pleasantness ratings for female social touch was smaller in subjects with higher autistic traits. Aberrant social reward of touch in individuals with ASD has been associated with a diminished BOLD response to pleasant and an exaggerated limbic response to unpleasant stimuli (Cascio et al, 2012). Consistent with these results, in the present study AQ score and the OFC response to touch were negatively correlated in the more pleasant female touch condition but positively associated in the more aversive male touch one.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Thus, the OXTmediated increase in pleasantness ratings for female social touch was smaller in subjects with higher autistic traits. Aberrant social reward of touch in individuals with ASD has been associated with a diminished BOLD response to pleasant and an exaggerated limbic response to unpleasant stimuli (Cascio et al, 2012). Consistent with these results, in the present study AQ score and the OFC response to touch were negatively correlated in the more pleasant female touch condition but positively associated in the more aversive male touch one.…”
Section: Discussionsupporting
confidence: 90%
“…Autism spectrum disorder (ASD) is a debilitating developmental disorder which is diagnosed on the basis of impaired social interaction and communication as well as restricted and repetitive interests and activities (American Psychiatric Association, 1994). However, a substantial majority of individuals with ASD also suffers from sensory processing deficits (Ben-Sasson et al, 2009) and a recent study found that they show a diminished response to pleasant and neutral somatosensory stimulation, and an exaggerated limbic response to unpleasant stimuli (Cascio et al, 2012). Likewise, healthy subjects with autistic traits exhibit diminished responses in the neural substrates for social touch, particularly in the OFC .…”
Section: Introductionmentioning
confidence: 99%
“…With respect to the other measure of anhedonia, the high incidence (81.6%) of physical anhedonia in the ASD group appears to contradict reports of sensory hypersensitivity in ASD (e.g, Rogers & Ozonoff, 2005;Minshew & Hobson, 2008;Baron-Cohen et al, 2009). Yet, these findings could be reconciled considering that hypersensitivity in ASD often evokes particularly strong positive or negative feelings (e.g., Robledo et al, 2012;Cascio et al, 2012) whereas in the present study anhedonia was measured using only yes/no responses (as is standard in the PAS). Further studies using response modalities that vary from 'very unpleasant', through 'neutral' to 'very pleasant' could provide further information in this regard.…”
Section: Discussionmentioning
confidence: 78%
“…Of interest too, cerebral responses to sensory stimulation have been linked with social and communication symptoms of ASD (Cascio et al, 2012) or with the level of autistic traits (AQ scores) in neurotypical individuals (Voos et al, in press). In the present study, anhedonia and autistic-traits scores were positively associated (more strongly with social anhedonia).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, interest is growing (Kida and Shinohara, 2013), and given that abnormalities in tactile processing have been implicated in a variety of neurodevelopmental disorders, such as Fragile X syndrome, autism spectrum disorders, attention deficit hyperactivity disorder, and cerebral palsy (Cascio, 2010;Hill et al, 2012), the typical and atypical development of touch as areas of research seems ripe for exploitation. Indeed, the latest evidence suggests that those with autism spectrum disorder exhibit a reduced response to affective touch (Cascio et al, 2012).…”
Section: Developmental Aspects Of Touchmentioning
confidence: 99%